Nutrition Management After Pediatric Solid Organ Transplantation. (April 2014) - Asfaw, Meheret; Mingle, Jillian; Hendricks, Jessica; Pharis, Maegan; Nucci, Anita M.
Survival rates for pediatric transplant recipients and organ grafts have increased due to improvements in surgical techniques and with immunosuppressant treatment therapies. Interdisciplinary management after pediatric organ transplantation is essential to assist not only with the complex medical issues and complications that can result from immunosuppressant therapy but also with the achievement of normal growth and development. Impaired growth is a complication frequently experienced by pediatric transplant patients. The presence or absence of impaired growth is affected by the length of illness prior to transplant, graft function, the use of corticosteroids, and the development of infectious complications after surgery. A review of posttransplant nutrition assessment, nutrition requirements, and nutrition goals is provided. In addition, a case series of experiences with nutrition management of pediatric solid organ transplant recipients is described.